OPTICAL BASED TRANSPARENT DROPLET DETECTION USING INFRA RED CIRCUIT DESIGN - Yusli Alifia, Talitha
Liquid volume measurement in laboratory test, for example, titration, usually is focused on the reduced amount of liquid left in container. However, to observe meniscus using sensor is hardly implementable so that droplet counting is chosen as alternative. In titration, the titrant used is usually transparent, low concentrated liquid, that physically behaves like water. Water droplet or transparent liquid is visible due to light refraction and reflection on its surface. Therefore, there is a change in light intensity when it passes droplet which is can be detected by optical sensor. One of the local maximum of light absorption by water is in 950 nm wavelength which is near-infrared wavelength. The light reduction by water droplet is supposed to be small even in local maximum so that highly sensitive sensor is required. Using direct configuration of infrared LED and photodiode, impulse signal achieved with 0.2 V rest voltage and 1.2 V highest peak voltage for tip opening diameter 0.6~0.8 mm; and 2.6 V highest peak voltage for tip opening diameter ~2.1 mm. Achieved signal has bouncing in it and variation in impulse height, but is still readable by comparator.